Enhanced hemocompatibility, antimicrobial and anti-inflammatory properties of biomolecules stabilized AgNPs with cytotoxic effects on cancer cells - Azam Chahardoli; Farshad Qalekhani; Pouria Hajmomeni; Yalda Shokoohinia; Ali Fattahi (Scientific Reports)
Abstract In the current research, we developed a safe method using Iranian yarrow extract for the synthesis of silver nanoparticles (IY-AgNPs) as reducing and stabilizing agents in different conditions. The prepared and stabilized IY-AgNPs under optimal conditions were characterized using FT-IR, XRD, TEM, and UV-vis techniques. Also, the blood-clotting, hemolytic, antioxidant, bactericidal and, fungicidal properties, cytotoxicity effects and inhibition of protein denaturation efficiency of IY-AgNPs were assessed in vitro. The stabilized IY-AgNPs with spherical shape and an average particle size of 19. 25 ± 7.9 nm did not show any hemolytic potential below 1000 µg/mL. These hemo-compatible NPs showed good blood-clotting ability by reducing clotting time (6 min relative to the control). These particles excellently inhibited the denaturation of bovine serum albumin (BSA) by 69.3–80.7% at concentrations ranging from 31.25 to 500 µg/mL compared to a reference drug. The outcomes showed that the IC50 values of IY-AgNPs were below 12.5 µg/mL against A375 cells and between 25 and 50 µg/mL against MCF-7 cancer cells. In addition, IY-AgNPs were bactericidal against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus (especially), and were fungicidal against Candida albicans. Biosynthesized IY-AgNPs indicated a significant antioxidant activity (63.2%) at a concentration of 350 µg/mL. These attained results suggested that bio/hemo-compatible IY-AgNPs may be a promising candidate for applications in the medicinal fields (particularly for wound healing) as anti-bleeding, antimicrobial, antioxidant, anti-inflammatory, and anticancer agents.